Gender-sensitive, climate-smart agriculture for improved nutrition in Africa south of the Sahara - Bryan, Elizabeth; Theis, Sophie; Choufani, Jowel; De Pinto, Alessandro; Meinzen-Dick, Ruth S.; Ringler, Claudia (International Food Policy Research Institute, 2017)
Chapter 9 tackles the nexus of CSA, gender, and nutrition, providing an integrated conceptual framework with entry points for action as well as information requirements to guide interventions in the context of climate change. The authors clearly argue that to go beyond incremental approaches to adaptation, these types of integrated approaches are essential in order to address the development challenges that the future climate creates.